A case study on physiochemical characteristics of solid waste in UiTM Pulau Pinang / Rahayu Muslim - Muslim, Rahayu (Faculty of Civil Engineering, 2007)
Municipal solid waste composition studies are essential to proper management of waste for a variety of reasons including a need to identify sources of component generation, to facilitate design of processing equipment, also to estimate physical, chemical, and thermal properties of the waste. The study was conducted at UiTM Pulau Pinang for the purpose on identifying the physiochemical characteristics of solid waste generated here. This report focuses on solid waste generation from Baiduri College, Perdana Complex, UiTM Hotel and Cafeteria. The methodology has been divided into three phases: fieldwork; sampling and manual sorting, laboratory work; ultimate analysis and data interpretation. Manual sorting used to separate the waste by composition such as food waste, paper, plastic, tin cans etc. Analysis on ultimate analysis, energy content and methane generation also been carried out in this research. The major component of solid waste is paper (35%), and followed by food waste (26%), and plastics (21%). The moisture content is influence by weather and the characteristics of solid waste. The energy produced is influenced by moisture content which is low moisture will increased the energy to resource recovery energy. The most recyclable waste produce is paper and plastic with the highest value is 70.3% from total weight of sample on particular week. The result of this study shows the level of awareness and 3Rs practice is low. Keyword – physical characteristics, chemical characteristics, municipal solid waste, solid waste management, recycling